1998
DOI: 10.1038/sj.sc.3100689
|View full text |Cite
|
Sign up to set email alerts
|

A therapeutic trial of acupuncture in neurogenic bladder of spinal cord injured patients – a preliminary report

Abstract: Eighty patients with spinal cord injury (SCI) and neurogenic bladder were studied. Among them, 28 (70%) cases in the control group and 32 (80%) cases in the electroacupuncture group achieved ultimately balanced voiding and were selected for further analysis. The acupuncture group received electroacupuncture at four acupoints: Chung Chi (Conception Vessel CV3), Kuan Yuan (CV4), and bilateral Tzu Liao (Urinary Bladder UB32), in addition to conventional intermittent catheterization program (ICP). Whereas the cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0
2

Year Published

2005
2005
2010
2010

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 10 publications
1
34
0
2
Order By: Relevance
“…28 Meanwhile, two other good-quality RCTs, although underpowered, reported nonsignificant results, 29,30 while two relatively inferior-quality studies reported significance. 31,32 Meanwhile, most acupuncture studies for bladder control in patients with spinal-cord injury, including two RCTs 33,34 and two case series, 35,36 indicated favorable outcomes despite limited quality. All in all, the recommendation rating for pain and bladder control in patients with spinal-cord injury is close to C with potential toward B.…”
Section: Acupuncture For Selected Neurologic Disorders: An Overview Omentioning
confidence: 99%
“…28 Meanwhile, two other good-quality RCTs, although underpowered, reported nonsignificant results, 29,30 while two relatively inferior-quality studies reported significance. 31,32 Meanwhile, most acupuncture studies for bladder control in patients with spinal-cord injury, including two RCTs 33,34 and two case series, 35,36 indicated favorable outcomes despite limited quality. All in all, the recommendation rating for pain and bladder control in patients with spinal-cord injury is close to C with potential toward B.…”
Section: Acupuncture For Selected Neurologic Disorders: An Overview Omentioning
confidence: 99%
“…Electro-acupuncture (EA) is an effective method of acupuncture, and has been showed to increase the number of axonal synaptic terminals from spared L 6 dorsal root ganglion (DRG) following adjacent dorsal root ganglionectomy in spinal lamina II and nucleus dorsalis (ND) by regulating neurotrophins [23][24][25][26][27][28], as well as promoting recovery from injured spinal cord and brain in clinical cases [29][30][31]. However, the underlying mechanisms are yet to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Electro-acupuncture (EA), is an effective method of acupuncture, and has been demonstrated to increase the number of axonal synaptic terminals from spared L 6 dorsal root ganglion (DRG) following adjacent dorsal root ganglionectomy in spinal lamina II and nucleus dorsalis (ND) [13][14][15], as well as promoting recovery from injured spinal cord and brain in clinical cases [16][17][18], but the underlying mechanisms are yet to be elucidated.…”
Section: Introductionmentioning
confidence: 99%